Impact of Brown Rice as Adjunct on Beer Brewing - Yufeng Wang; Xinyi Zhao; Suya Liu; Jiangyu Zhu; Yongqi Yin; Zhengfei Yang (Foods, 2025)
The utilization of alternative cereals for brewing beer has garnered significant interest in contemporary times. The utilization of alternative cereals as adjuncts has great potential for creating novel beer flavour profiles and cost savings. Brown rice (BR) is the unpolished rice grain that retains its outer layer post-hulling and is nutritionally superior to polished rice (PR). The utilization of BR in beer production remains unexplored, with its brewing attributes in comparison to PR yet to be elucidated, probably due to the potential adverse impact on beer flavour. This study involves incorporating PR and BR as adjuncts in a 40% ratio, alongside 100% Pilsen malt (PM) beer as the control, to contrast the brewing attributes (physicochemical indicators, antioxidant attributes, volatiles, and sensory analysis). Raw material analysis results showed that BR contains starch (72.97%), protein (6.85%), fat (3.38%), and ash (1.04%). The protein content of PR (4.12%) was lower than that of BR (6.85%), attributed to the absence of bran in PR, resulting in a reduced free amino nitrogen (FAN) content in its wort. Furthermore, it was observed that 40% BR beer showed enhanced antioxidant properties (0.55 mmol TE/L for DPPH and 0.75 mmol TE/L for ABTS) in comparison to 40% PR beer (0.12 mmol TE/L for DPPH and 0.4 mmol TE/L for ABTS). The changes that occurred in volatile and sensory analysis indicated discernible modifications in beer flavour consequent to the partial substitution of barley malt with BR. These findings show BR is an appropriate brewing adjunct.